Pasig our river, our future - Alcazaren, Miguel; Iglesias, Roy.; Vigo, Efren B.; People's Television 4. ([Quezon City PTV 4)
Traces the history of the Pasig River and its exploitation and misuse.
Host, Jonee Gamboa.
Keywords: Pasig River